PENGARUH PERSEPSI DAN PENGGUNAAN MEDIA SOSIAL TERHADAP TERPAAN BERITA HOAX TAGAR #JUSTICEFORAUDREY DI KALANGAN PELAJAR SMA NEGERI DI KECAMATAN PESANGGRAHAN - Setyawan, Andy (JURNAL KOMUNIKATIO, 2019)
This study aims to find out Perception and Social Media Use Toward Hoax #Justiceforaudrey in Senior High School Students at Pesanggrahan Subdistrict. This study used a qualitative approach and survey method. The sample used was 106 high school students in the Pesanggrahan sub-district, South Jakarta. The results showed that found a significant effect between the perception of hoax news exposure with a regression coefficient of 0.182 greater than 0.05, and there is a significant influence between the use of social media on the exposure of hoax news with a regression coefficient of 0.537 greater than 0.05. Furthermore, the results obtained by R Square in this study amounted to 0.405 or 40.5%. This means that the influence of the perception and use of social media variables on exposure to hoax news by 40.5%. The remaining 59.5% is influenced by variables outside this study.Â Keywords: Perception, Media Social, Hoax